English Class: Optimalisasi Kemampuan Billingual Anak-Anak Desa Adat Tenganan Pegringsingan - Santati, Parama; Lakilaki, Eogenie (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: The purpose of this service is to improve the English language skills of elementary and junior high school students of Tenganan Pegringsingan Traditional Village. Methodology/approach: This service was carried out in Tenganan Pegringsingan Village for two days, with 25 students participating. The methods used were lecture, practice, and making mini pocket dictionary. Evaluation was carried out by assessing English language skills and assessing participants' work using an assessment sheet. Results/findings: Based on the results of the implementation, English Class and Mini Pocket Dictionary assessment states that participants have sufficient English language skills with an average score of 71 which indicates a "good" understanding. However, speaking and reading skills still need to be improved. The evaluation that must be improved in this activity is the limitation of the category of participants. In the future, high school students and parents can also be included in activities like this to support their communication to foreign tourists visiting the village. Conclusion: This Community Service which is packaged in the form of English Class and Mini Pocket Dictionary has been held in Tenganan Pegringsingan Village, Bali Province on July 4-5, 2023. Based on the results of the implementation, this Community Service is able to provide increased bilingual skills to indigenous village children to equip them when communicating to foreign tourists, participating in various competitions, and even participating in international activities.